Turnover intentions and safety compliance in the military: A psychological contract perspective - Johannes Kraak; Yannick Griep; Pierre Barbaroux; C. Lakshman (BRQ Business Research Quarterly, 2025)
NATO members have been coping with low motivation and morale. Such environments typically have high turnover intentions and neglect behavior. However, safety behavior is paramount for military organizations and neglect behavior can have serious consequences. Social exchanges are often cited as the main reason for these phenomena. We therefore examine turnover intentions and safety compliance behavior of 1,593 airmen from a European NATO Air Force by focusing on different psychological contract (PC) dimensions. We use polynomial regression and response surface analysis. Results show that higher levels of PC fulfillment are related to lower levels of turnover intentions and higher levels of safety compliance behavior. Furthermore, perceptions of PC overfulfillment are negatively associated with turnover intentions, whereas safety compliance is unaffected by positive (overfulfillment) and negative (underfulfillment) PC discrepancies along all PC dimensions. We discuss implications for the PC literature, make suggestions for future research, and provide practical implications.
Keywords: M0; M1; C3; 650; Psychological contract; social exchange theory; safety behavior; turnover intentions; polynomial regression